If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying G + -4 = 1 Reorder the terms: -4 + G = 1 Solving -4 + G = 1 Solving for variable 'G'. Move all terms containing G to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + G = 1 + 4 Combine like terms: -4 + 4 = 0 0 + G = 1 + 4 G = 1 + 4 Combine like terms: 1 + 4 = 5 G = 5 Simplifying G = 5
| y=2x^3+7x^2+7x+2 | | (x-1)(x+8)= | | sin(10*x)=cos(5*x) | | 20-4v=14 | | sinx=0.56 | | M+1=5 | | 0.3x-2.1=5-1.7(x-1) | | 28-2y=8+8y | | 18xsquaredy-12xysquared= | | 6x+3=2x-10 | | 5-h=0 | | -4-5x=-6-6x | | -32-5x=-16-x | | 9x+64=x+56 | | 2=9-(3x-17) | | 9x-80=x+16 | | 10x+40=2x | | 4s+37=133 | | 9+6x=-16x-123 | | 4z-13=-18+9z | | 5t-29=-8+8t | | 3-5x=2x+7 | | 4x^2-6x+5=2 | | 0.0016-1= | | 5-f=3 | | 2x^2*2x= | | 8x-1=5x+15 | | 25+8p=0 | | x^2-2y+4x+6=0 | | 5x+18=1.17 | | 2+3(5x-7)=25x-35 | | 6m-7=-13+5m |